The Clinicopathological and Prognostic Implications of FoxP3+ Regulatory T Cells in Patients with Colorectal Cancer: A Meta-Analysis - Xu, Peipei; Fan, Wei; Zhang, Zheng; Wang, June; Wang, Ping; Li, Yirong; Yu, Mingxia (Frontiers in Physiology, 2017)
Background and Objective: Forkhead box P3 (FoxP3) is known as the specific marker for regulatory T lymphocytes (Tregs), which are responsible for self-tolerance and disturb the antitumor immunity. However, the prognostic implication of tumor-infiltrating FoxP3+ Tregs in patients with colorectal cancer (CRC) still remains controversial. The aim of the present study was to clarify the prognostic role of FoxP3+ Tregs in CRC through meta-analysis. Methods: PubMed, Embase and Web of Science were searched for relevant articles up to December 12, 2016. Pooled hazard ratio (HR) and 95% confidence interval (CI) were calculated to explore the prognostic value of FoxP3+ Tregs in CRC. Odds ratio (OR) was calculated to investigate the correlation between FoxP3+ Tregs and pathological parameters. Results: A total of 18 studies comprising 3,627 patients with CRC were enrolled in our meta-analysis. The combined HR for FoxP3+ Tregs on cancer-specific survival was 0.70 (95% CI = 0.62-0.80, P < 0.001). High FoxP3+ Tregs level was also associated with favorable prognosis on overall survival (HR = 0.76, 95% CI = 0.58-1.01, P = 0.058), with P value very close to the statistical threshold. Yet, there was no correlation between FoxP3+ Tregs infiltration and disease-free survival (HR = 0.83, 95% CI = 0.63-1.09, P = 0.182). Moreover, FoxP3+ Tregs infiltration was significantly correlated with pT stage (OR = 0.50, 95% CI = 0.39-0.65, P < 0.001), tumor grade (OR = 0.77, 95% CI = 0.61-0.98, P = 0.032), lymphatic invasion (OR = 0.25, 95% CI = 0.07-0.89, P = 0.033) and vascular invasion (OR = 0.67, 95% CI = 0.52-0.86, P = 0.001). Conclusion: The present meta-analysis suggests that high FoxP3+ Tregs infiltration is inclined to indicate favorable prognosis and is associated with the pathogenesis of CRC. Immunotherapy targeting Tregs in patients with CRC should be further investigated.